Human Resource Allocation in the Main Drainage Construction Project for Flood Control in Palangka Raya City - Lendra Lendra; Febry Handayani; Alprido Perdian; Jermias Tjakra; Theresia Widi Asih Cahyanti (Teknika, 2025)
Human resource management challenges are often faced in construction projects, and human resource leveling is an effective method to overcome construction scheduling fluctuations. This study aims to identify effective human resource leveling strategies in the construction of flood control drainage in Palangka Raya City and analyze their impact on the efficiency of project scheduling and completion. This method reduces the number of human resources without sacrificing project completion, accelerating completion without reducing quality. The resource leveling method in project human resource planning can produce an optimal labor requirement graph compared to the initial fluctuating requirement graph. In this project, before leveling, the number of resources was 1023 OH, after which it became 925 OH, a reduction of 9.58%. In the types of workers, masons, head masons, and foremen, the number has decreased significantly, so that resources become more controlled. Despite the reduced number, the project completion can be accelerated by 42 days from the planned 300 days to 258 days